Efeito da solução nutriente na produção microbiana sequencial de ácido cítrico e etanol a partir de bagaço de cana-de-açúcar e vinhaça - Campanhol, Beatriz Silva (Universidade Federal de São Carlos, 2018)
Solid-state cultivation (SSC) refers to microbial growth on solid supports under limited free-water conditions, that is, similar to the occurrence of mainly fungi in nature. This process has had considerable technological potential in the chemical, food, pharmaceutical and agricultural industries. In most cases, the solid medium is impregnated with a solution containing the carbon source and nutrients, which provide, in addition to the required substrate, suitable moisture conditions. Among the various microorganisms that can be grown from solid supports, filamentous fungi are mainly used due to their physiological and biochemical characteristics. The literature reports that fungal consortia have advantages over the use of single cultures because they use the substrate better, leading to a higher yield, being more adapted and resistant to contamination by other microorganisms due to the synergistic interactions that occur between them. The products obtained by SSC are generally separated from an extract which may be aqueous or obtained from organic solvents. Considering the effect of fungal hydrolases on solid supports, such as sugarcane bagasse for example, there is a release of glucose in this extract, and other products could be generated from this carbon source. Citric acid is a bioproduct with several industrial applications, and its production is traditionally microbial from the medium containing sucrose, being induced by the presence of lower alcohols, mainly methanol and ethanol. Whereas citric acid and ethanol are important commercial bioproducts used in various sectors of the economy, these could be obtained by a sequential SSC-fermentation process from sugarcane bagasse impregnated with vinasse, using two by-products. In this context, the aim of these research was evaluated the production of citric acid by Aspergillus niger and Trichoderma reesei consortium in sugarcane bagasse with vinasse and ethanol as inducer of the metabolic production of this organic acid, followed by ethanol fermentation of the fungal extract by yeasts Saccharomyces cerevisiae and Dekkera bruxellensis. Results indicate that the highest yields of glucose in citric acid, productivity and specific production speed for the conditions having vinasse and vinasse/ethanol as nutrient solution. In addition, citric acid and glucose profiles indicate higher yields, yields and specific rates (1.88 mg citric acid mg glucose-1, 13.77 mg citric acid L-1 h-1 and 29.30 mg citric acid gbiomass-1 h-1) for the condition having only vinasse as nutrient solution, with maximum citric acid concentration of 734 mg L-1 in 48 hours. Regarding the use of the fungal extract, there was no considerable production of ethanol by Dekkera bruxellensis, possibly due to the presence of inhibitors. However, the ethanol fermentation by Saccharomyces cerevisiae achieved a yield of 71% of the stoichiometric maximum. The experimental results demonstrate the feasibility of the co-production of citric acid and ethanol via the sequential SSC-fermentation process with fungal microbial consortium (Aspergillus niger and Trichoderma reesei) and Saccharomyces cerevisiae from sugarcane bagasse and vinasse.
Effect of the nutrient solution on the sequential microbial production of citric acid and ethanol from sugarcane bagasse and vinasse
Keywords: Cultivo em estado sólido; Bagaço de cana-de-açúcar; Ácido cítrico; Etanol; Consórcio microbiano; Solid-state cultivation; Sugarcane bagasse; Citric acid; Ethanol; Microbial consortium; CIENCIAS BIOLOGICAS::MICROBIOLOGIA::MICROBIOLOGIA APLICADA::MICROBIOLOGIA INDUSTRIAL E DE FERMENTACAO